Watch runs away - Warner, Gertrude Chandler, 1890-1979.; Duffy, Daniel M. (Morton Grove, Ill. : A. Whitman, 1999)
Benny tries to figure out why his dog, Watch, keeps escaping from the yard.
"A boxcar children early reader"--Cover.
2.3
K-3
Keywords: Dogs -- Juvenile fiction; Boxcar children (Fictitious characters) -- Juvenile fiction; Dogs -- Fiction; Boxcar children (Fictitious characters) -- Fiction; Dogs -- Fiction; Boxcar children (Fictional characters) -- Fiction